Kombinasi Metode High Pass Filtering dan Contrast Stretching Dalam Peningkatan Detail dan Kontras Citra - -, Nurhidayati; Lailan Sofinah Harahap; Juwita Sari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Digital images have many functions in fields such as medicine, remote sensing, security, and social media, where cinematography and visual delivery are very complex. However, images often have problems with noise, blur, and low contrast. Furthermore, in an underwater image, another challenge arises because light is absorbed and scattered unevenly, which makes the image look blurry and dark. This study aims to explain the improvement of the digital image processing process in two ways, namely through High Pass Filtering and Contrast Stretching. Details and edges of the image that you want to focus on will be added with High Pass Filtering which is done through 2D FFT. While the name of the second method, namely Contrast Stretching, means clarifying the differences in objects and backgrounds by widening the range of pixel intensity. The trial was carried out on a grayscale image measuring 200x200 pixels in JPG format. The processes carried out include conversion to grayscale, high frequency, application of Low Pass Filter, and contrast stretching. Based on the processing results, the increase in image sharpness reached 35% and contrast 42% when compared to unprocessed images. These figures will then be very helpful in visual analysis and interpretation